Antibacterial Activity of Cinnamic Acid - Chitosan Encapsulation - Nur Amaliyah; Purbowatiningrum Ria Sarjono; Ngadiwiyana Ngadiwiyana; Ismiyarto Ismiyarto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
The biggest cinnamon bark is cinnamic acid. The inhibitory activity of bacterial growth of S. aureus and E. coli and its abundance in nature becomes the superiority of cinnamic acid as antibacterial. However, the use of cinnamic acid as an antibacterial is still less than optimal because of low solubility in water. One of the latest technologies to address the problem is encapsulation in nanometer size. Encapsulation of cinnamic acid using chitosan nanoparticles as an encapsulation material was shown to increase the activity of cinnamic acid as antibacterial by protecting the active compound, as well as increasing its solubility in water through chitosan-TPP modification. Emulsion formation was performed using Corning LSE Compact at 6,000 rpm for 30 minutes. The formation of chitosan nanoparticles as encapsulation material was done using freeze dryer with freeze drying method. Chitosan was obtained from shrimp chitin with Deacetylation Degree (% DD) of 85.98%. The synthesis of chitosan nanoparticles yielded an average particle size of 330 nm with a percentage volume of 29.9% and 79.1% with an average size of 5570 nm. The morphological form of nanometer-sized chitosan was smaller and uniform than that of chitosan morphology. Encapsulation efficiency value of 67.304% makes cinnamic acid has higher activity inhibition of bacterial growth than pure cinnamic acid and chitosan nanoparticles.